Children’s Choral Songs as a Socio-Cultural Tool in Shaping Collective Consciousness (Música Hodie, 2025)
The relevance of the topic is determined by the need to preserve cultural identity in the context of globalization, the importance of music for the development of emotional intelligence, social skills, and aesthetic perception in children. The aim of the study was to identify the impact of choral singing on the development of a child’s personality, particularly in the formation of collective consciousness, social integration, and the preservation of cultural traditions. To analyse the development of choral art in Kosovo and its impact on children, historical-chronological, socio-cultural approaches, and surveys were used. These methods allowed the exploration of the evolution of choral tradition, its role in shaping national identity, and the emotional intelligence of children. The results of the study showed that choral singing has a positive impact on children’s development. Most participants (85%) noted that they enjoy participating in the choir, and 78% said it helps them make new friends. Teachers (90%) emphasized that choral singing develops communication skills, discipline, and forms national consciousness. 75% of children believe that the choir helps them better understand other cultures, confirming the role of music as a tool for intercultural dialogue. Innovative methods, such as interactive exercises, multimedia use, creative approaches to the repertoire, and interdisciplinary integration, make the learning process more effective and interesting. The conclusions of the study confirmed that choral singing is an important pedagogical tool that contributes to the formation of a child’s personality, the development of their social, emotional, and cultural skills.